Maḥmūd-nāma - Maḥmūd Lāhorī (Nawal Kišūr, 1886)
A series of Persian ghazals, one for each letter of the alphabet, on the theme of the ideal love, with references to the idealized love of Sultan Maḥmūd Ġaznavī for his beautiful slave Ayāz